ANALISIS KONSUMSI UMPAN DAN INDEK PENGURANGAN SAMPAH ORGANIK MENGGUNAKAN MAGGOT (Hermetia Illucens) - Ellyke; Syamdiyanitari Neneng (Jurnal Kesehatan Tambusai, 2021)
Waste is a global problem, both developed and developing countries. It is estimated that in 2025 the population will increase by 284.83 million people with an estimated increase in the amount of waste to 5.93 million tons per year. The accumulation of garbage produces toxic liquids (leachate) that can degrade the quality of rivers, groundwater, and soil. This study aimed to analyze the ability of Hermetia illucens larvae to consume bait and the reduction index on 15g of organic waste in the form of 5g cabbage, 5g rice and 5g fish offal with variations of 0 larvae, 15 larvae, 20 larvae and 25 larvae for 15 days. This research is an experimental research with Posttest-only Control Design. Based on the results of the study, it can be seen that the control group has the characteristics of sharp-scented waste, it is contaminated with house fly larvae. The treatment group had the opposite characteristics, namely that the waste had no sharp odor, was not contaminated with other fly larvae other than Hermetia Illucens larvae and there was no larval death in all samples. The highest feed consumption was in the P3 group with a feed consumption value of 92.22% and the lowest was in the P0 group, which was 71.11%. The highest decomposition index was in the P3 group of 6.15% and the lowest was in the P0 group, which was 4.74%.